Unlocking the Genetic Code: The Role and Relevance of Genetic Counsellors in Today’s World – A Global Perspective with a Deep Dive into India and State-Level Comparisons - Shukla, Ishan Maheshbhai; Prusty, Ramakanta (Journal of Neonatal Surgery, 2025)
Genetic counselling plays a pivotal role in modern medicine by translating complex genomic information into patient-centred guidance. Globally, the profession has evolved into a cornerstone of personalized healthcare. In India, however, the field remains underdeveloped, despite a high burden of genetic disorders and growing genomic awareness. This paper examines the global status of genetic counselling, outlines India's fragmented landscape, compares state-level capacities, and explores regulatory challenges. Special attention is given to Gujarat and Karnataka as regional case studies. Appendix A provides visual data, workforce estimates, and trend projections, reinforcing the need for regulatory recognition, expanded training, and equitable service distribution across India